A C3-symmetrical chiral trisoxazoline zinc complex as a functional model for zinc hydrolases: kinetic resolution of racemic chiral esters by transesterification - Dro, Clémence; Bellemin-Laponnaz, Stéphane; Welter, Richard; Gade, Lutz H. (Angewandte Chemie. International edition, 2004)
Mimicking the activity of tris(histidine)zinc-based enzymes, chiral dinuclear trisoxazolinezinc complexes such as the triflato cation (see picture) are the first non-enzymatic catalysts for the asymmetric transesterification of activated esters. First results of the kinetic resolution of amino acid phenolates establish the stereoselectivity for this reaction. (F pink, N blue, O red, S yellow, Zn cyan)
Gesehen am 16.12.2022